2010
DOI: 10.1093/rpd/ncq102
|View full text |Cite
|
Sign up to set email alerts
|

Management of patient doses and diagnostic reference levels in X-ray radiography in Lithuania

Abstract: Management of patient doses and determination of national or local diagnostic reference levels (DRLs) are important parts of a quality control program in X-ray diagnostics. In Lithuania, national DRLs for specific radiographic examinations are comparatively higher than those recommended by the European Commission (EC) and the International Atomic Energy Agency (IAEA). A survey of entrance surface doses (ESDs) was performed to investigate the reasons for exceeding the European and the IAEA DRLs. The first measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
3
1
1
Order By: Relevance
“…For the sake of clarification, the mean ESD values found in the present study were lower than those in other investigations in India (24) , Korea (25) , Iran (26) , Malaysia (28) , Switzerland (29) , Bangladesh (30) , Bulgaria (31) , Nigeria (34) , Lithuania (35) and Russia (36) . One possible explanation for this is that the reference dose levels of some of these countries are based on data collected several years ago and using older, less efficient technology.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…For the sake of clarification, the mean ESD values found in the present study were lower than those in other investigations in India (24) , Korea (25) , Iran (26) , Malaysia (28) , Switzerland (29) , Bangladesh (30) , Bulgaria (31) , Nigeria (34) , Lithuania (35) and Russia (36) . One possible explanation for this is that the reference dose levels of some of these countries are based on data collected several years ago and using older, less efficient technology.…”
Section: Discussioncontrasting
confidence: 93%
“…In figure 4(a-c), a comparison is established between the average ESD, ESAK and exposure factor values obtained in this study and the ESD values reported in previous studies from India (24) , Korea (25) , Iran (26) , the United Kingdom (UK) (27) , Malaysia (28) , Switzerland (29) , Bangladesh (30) , Bulgaria (31) , Italy (32) , Sudan (33) , Nigeria (34) , Lithuania (35) and Russia (36) . It can be observed that the mean ESD values of the skull LAT exami- nation in this study were higher than those reported in the UK (27) but less than those in several other countries (24,(28)(29)(30)(31)(34)(35)(36) . In this study, we chose to compare our mean ESD values with the internationally reported dose metrics, but the recent recommendations favour median values.…”
Section: Discussionmentioning
confidence: 77%
“…Table 7 shows a comparison of the values for our proposed DRLs and DRLs in foreign countries (included our data of 2014) [11][12][13][14][15][16][17][18][19][20]. DRL which we proposed this time is not so high in comparison with foreign countries either.…”
Section: Resultsmentioning
confidence: 99%
“…Examinations This Study Asada et al [11] Uniyal et al [12] Metaxas et al [13] Ireland [14] Bulgaria [15] UK [16] Lithuania [17]…”
Section: Entrance Surface Dose [Mgy]mentioning
confidence: 99%
“…医疗照射是最大的人工电离辐射源, 而 X 射线诊 断频率占比最高 [1] 。随着国民经济和社会的发展,一 方面,人们使用医用 X 射线诊断检查的应用频率不断 增加 [2,3] ; 另一方面人们又更加关注自身的放射防护问 [14,15,19] ,立陶宛在 2010 年 [23] 与 2005 年的值 [22] 相比 降低;其次,制订 DRL 的部位和类别逐渐增多;另 外,很多地区根据本地情况,在国家水平的基础上还 不断完善的医用 X 射线摄影诊断指导水平 …”
Section: 引言unclassified